A Combined Theory‐Experiment Analysis of the Surface Species in Lithium‐Mediated NH3 Electrosynthesis. Issue 7 (31st January 2020) - Schwalbe, Jay A.; Statt, Michael J.; Chosy, Cullen; Singh, Aayush R.; Rohr, Brian A.; Nielander, Adam C.; Andersen, Suzanne Z.; McEnaney, Joshua M.; Baker, Jon G.; Jaramillo, Thomas F.; Norskov, Jens K.; Cargnello, Matteo
Abstract: Electrochemical processes for ammonia synthesis could potentially replace the high temperature and pressure conditions of the Haber‐Bosch process, with voltage offering a pathway to distributed fertilizer production that leverages the rapidly decreasing cost of renewable electricity. However, nitrogen is an unreactive molecule and the hydrogen evolution reaction presents a major selectivity challenge. An electrode of electrodeposited lithium in tetrahydrofuran solvent overcomes both problems by providing a surface that easily reacts with nitrogen and by limiting the access of protons with a nonaqueous electrolyte. Under these conditions, we measure relatively high faradaic efficiencies (ca. 10 %) and rates (0.1 mA cm −2 ) toward NH3 . We observe the development of a solid electrolyte interface layer as well as the accumulation of lithium and lithium‐containing species. Detailed DFT studies suggest lithium nitride and hydride to be catalytically active phases given their thermodynamic and kinetic stability relative to metallic lithium under reaction conditions and the fast diffusion of nitrogen in lithium. Abstract : A dynamic trio : Electrodeposited lithium is an active electrochemical ammonia synthesis catalyst. Voltammetry and impedance spectroscopy show that the active surface is composed of reduced lithium species. Density functional theory shows the activity role for lithium metal, lithium nitride, and lithium hydride.